Analysis of Banking Credit Response to Quantitative Easing Policy during the Covid-19 Pandemic in Indonesia: IPB University (Jurnal Ekonomi dan Kebijakan Pembangunan, 2023)
The purpose of this study is to identify the response of banking credit/financing and to analyze which bank characteristic variables have caused and had the potential to differentiate in banking credit/financing responses after the implementation of the quantitative easing policy during the Covid-19 pandemi in Indonesia. This study uses the Klaassen Typology, Discriminant Analysis, and Multinomial Logistics methods. With quantitative data from 30 banks included in books 2 and 3, the results show that In quantitative easing 1, there are 15 banks respectively that have positive credit/financing growth, while in quantitative easing 2 there are 14 banks that have positive credit/financing growth and 16 banks with stagnant or negative credit/financing growth with variable that can distinguishes the bank's credit response is deposit growth. The study also concluded that with the Multinomial Logistic method show that a significant positive variable in all quadrants is the security asset to total assets ratio.